DESIGN OF ADI SOEMARMO AIRPORT RAILWAY STATION - Gilbert, Christopher
The commuting system that links the town of Solo to Adi Soemarmo Airport has yet to be accommodated by a transportation facility that is capable of massively carrying commuters. Consequently, this can become an issue considering the relatively high demand of commuters to travel from the town of Solo to Adi Soemarmo Airport and vice versa. However, the construction of Adi Soemarmo Airport Railway Station which operates as transit station might possibly be a solution. Hence, this particular thesis will be focusing on the structural design of of an airport railway station which incorporates reinforced concrete for its primary structural components as well as steel for its structural roof components. The primary structural system consists of a 2-story building which is 104 m long and 28 m wide while the overall height of the building is 23 m. The design procedures carried out in this thesis mostly refers to the capacity -based design of the structural components, serviceability, and the structural response to seismic loading. Based on design, the structural components of its reinforced concrete structure consist of 13 beam types, 5 column types, and 10 slab types. The beams and columns are designed as part of the special moment frame components. While the roof components are made up of steel pipe profile with 5 different cross-sectional dimensions. The connection between the roof components utilizes fillet welding with weld size of 5 mm.